IMPLEMENTASI FULL DAY SCHOOL DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VIII DI MTs. AL-HUSNA KOTA TANGERANG BANTEN - yayan yayan (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2021)
The purpose of this study was to find out how the implementation of Full Day School in Improving the Learning Achievement of Class VIII Students in MTs. Al-Husna, Tangerang City, Banten. The method used in this research is descriptive qualitative research method, namely by observing the research location, conducting interviews and collecting data from various sources related to the research. The results of this study conclude: The implementation of full day school at MTs Al-Husna has been going well. Students get better report cards. Students are accustomed to praying dhuha, praying dhuhur, asr in congregation, dhikr, and reading the Qur'an, without being ordered by their parents. Students are able to read the Qur'an in accordance with tajwid. Students are able to memorize the Qur'an juz 29 and juz 30.